Census model transition - Dias, Carlos A. (2017)
Given the high cost and complexity of traditional censuses, some countries have started to change the census process. Following this trend, Portugal is also evaluating a new census model as an alternative to an exhaustive collection of all statistical units. The main motivations for the implementation of this census model transition in Portugal are related to the decrease in statistical burden on citizens, improvements in the frequency of outputs, and the reduction of collection costs associated with census operations. This article seeks to systematise and critically review all alternatives to the traditional census methodologies, presenting their advantages and disadvantages and the countries that use them. As a result of the comparison, we conclude that the methods that best meet these objectives are those that use administrative data, either in whole or in part. We also present and discuss the results of an inventory and evaluation of administrative registers in Portugal with the potential to produce statistical census information.